DNA Optical Detection Based on Porous Silicon Technology: from Biosensors to Biochips - Ivo Rendina; Ilaria Rea; Lucia Rotiroti; Carmen Sanges; Annalisa Lamberti; Paolo Arcari; Luca De Stefano (Sensors, 2007)
A photochemical functionalization process which passivates the porous silicon surface of optical biosensors has been optimized as a function of the thickness and the porosity of the devices. The surface modification has been characterized by contact angle measurements. Fluorescence measurements have been used to investigate the stability of the DNA single strands bound to the nanostructured material. A dose-response curve for an optical label-free biosensor in the 6-80 ÃŽÂ¼M range has been realized.